The Leadership Style of School Principals in Improving Educational Quality at a Model School: Indera Shahbandar School Pahang (SISP) Malaysia - Bahri, Noradila Binti Shaiful; Yuliana, Lia (Transpublika Publisher, 2024)
This study analyzes the principal's leadership style at Sekolah Indera Shahbandar Pahang (SISP), examining its impact on educational quality, associated challenges, and strategies to overcome these challenges. This study used a qualitative research method with the type of case study research. The subject of the study was the principal of the Special Model School: Sekolah Indera Shahbandar Pahang (SISP). The research was conducted at Seri Bentong Vocational High School and Seri Tualang Vocational High School, Malaysia. Data collection was carried out through observation, interviews, and documentation. Furthermore, the stages of data analysis included data reduction, data presentation, conclusion, and verification. The study results find that: 1) The principal of Seri Bentong Tualang Vocational High School adopts a transformational leadership style, while the principal of Seri Tualang Tualang Vocational High School, the principal of the school, applies a democratic leadership style. 2) The leadership style applied by the principal also has different implications. 3) The two schools studied also face challenges in implementing leadership styles. 4) Leadership strategies implemented by the principal at Sekolah Indera Shahbandar Pahang (SISP) to overcome challenges in improving the quality of education.